Hubungan antara Bimbingan Orang Tua dan Kedisiplinan dengan Pencegahan Perilaku Menyimpang - Benny Prasetiya (Shautut Tarbiyah, 2019)
This study raised the title "Relationship Parental Guidance and Discipline with Behavior Notwithstanding Students' reasons for expressing things that can prevent deviant behavior, the intention is there a relationship between the level of the guidance given by parents of students with deviant behavior learners school and outside of school. And want to know how the actual participation must be made by the parents, when their children were school, particularly how parents position itself in preventing or overcoming deviant behavior in children. In this study determines the sample of 100 students from the entire population of students of class XI SMA in Probolinggo the school year 2014. As for the sampling method is simple random sampling. Namely sampling of the population is done by randomly without regard to strata or levels. In this case the sample is determined by randomly selected for the entire population of students of class XI SMA in Probolinggo. The statistical methods will be used in the data menganalisisi results of this study is to use the correlation Double (Multyple Correlation). Correlation on (multyple correlation) is a number that indicates the direction and strength of the relationship between the two variables together or with other variables.